PEMBELAJARAN JURNAL AKUNTANSI USAHA DAGANG UNTUK SISWA SMA TARSISIUS 1 - Nataherwin; Jonathan, Michelle Leevia (Jurnal Serina Abdimas, 2024)
To ensure a business continuity of a business continuously, a financial analysis is needed. To make it easier to carry out financial analysis, financial reports are needed. This financial report provides a brief overview of the company's financial health, profitability, growth potential, and the company's tax obligations. Quality financial reports are formed because of the existence of quality human resources. To create quality human resources who are ready to face challenges in the business world, relevant and applicable learning is the main key. In this context, Tarumanagara University through the Community Service Team (PKM) presents learning innovations that focus on accounting skills through this article, with a focus on learning trade business accounting journals for Tarsisius 1 High School students. The aim of this learning is to increase the knowledge of readers and students /I related to trading business accounting. The method provided is learning with 10 face-to-face meetings. The learning method in this activity consists of oral teaching using power points in front of the class. Then proceed with problem-based learning methods and group discussions. The results of this activity showed that this learning session was quite effective and went well for the students, especially with the quizzes that were carried out. The conclusion of this activity is that students increase their knowledge about journal transactions in trading companies and most students understand and comprehend accounting transactions and are expected to be able to implement them in their daily lives.